Impact of practical work in promoting learning of kinematics graphs in Tanzanian teachers’ training colleges - Mbwile, Beni; Ntivuguruzwa, Celestin (International Journal of Education and Practice, 2023)
This paper investigated the impact of practical work in promoting the learning of kinematics graphs in Tanzanian teachers’ training colleges. The study employed a quantitative research approach and experimental design. A total of 150 pre-service Physics teachers from two teachers’ training colleges were distributed into control and experimental groups. Pre-service teachers in the control group were taught through the usual lecture method while those in the experimental group were taught through practical work. Developed and validated physics teachers’ kinematics graphs concept inventory was used for measuring pre-service teachers’ achievement by administering tests before and after interventions. Simple descriptive (mean, minimum, standard deviations, and maximum) and inferential statistics (t-tests, effect size, p-value, and normalized score gains) were analyzed by using Statistical Package for Social Sciences version 22 and Microsoft Excel. The group of pre-service teachers in the experimental group performed better than those in the control group by achieving average normalized learning gains of 39.6% compared to normalized learning gains of 1.52% for the lecture class. There was also a statistically significant difference (p-value < 0.001) in performance when pre-service teachers were taught through practical work. The study concluded that the use of practical work in teaching and learning was a good approach because it improved pre-service teachers’ understanding of kinematics graphs significantly. Based on these findings, the study recommends using practical work in the teaching and learning process for better performance of learners in kinematics graphs and other topics of physics.